Wheat Farming Dynamics in Pothohar: From Rainfed Practices to Irrigation Systems - Shahid Hameed Khan Khalil; Muhammad Shahzad Khattak; Ghani Akbar; Muhammad Ajmal (Irrigation and Drainage, 2026)
This study evaluated the dynamics of wheat yield and water productivity under various irrigation methods and farming practices in the rainfed‐to‐irrigated transitioning areas of the Pothohar region, Pakistan. Long‐term yield data (1981–2023) from the Pakistan Bureau of Statistics and farmers' field surveys were used to benchmark existing practices. The comparative performance of conventional flood irrigation (CF) and high‐efficiency irrigation systems (HEISs) was assessed through crop water productivity and simulated root‐zone water balance using the FAO AquaCrop model. The results revealed an average wheat yield of 1.34 ± 0.34 t ha −1 , showing 78% and 69% lower yields than the Punjab provincial and national averages. Irrigated areas (2.55 ± 0.29 t ha −1 ) yielded 96% more than rainfed areas (1.30 ± 0.33 t ha −1 ), underscoring the critical role of irrigation in enhancing productivity. HEIS reduced evaporation (14%) and drainage losses (17%), resulting in 18% higher water productivity (1.66 kg m −3 ) compared with CF (1.41 kg m −3 ). Root‐zone water balance analysis confirmed that HEIS improved soil moisture conservation and transpiration efficiency, making it a sustainable irrigation option for Pothohar's semi‐arid wheat systems. The study highlights inefficiencies in prevailing practices and the potential of HEIS to bridge yield gaps and improve water productivity in the region's transitioning agroecosystems.